Psychological Well-Being, Global and per Dimension, in Mexican University Students: A Systematic Review - Ramírez Enríquez, Silvia Isela (Consorcio de Universidades Mexicanas A.C., 2023)
The objective of this study was to analyze the degree of global psychological well-being and its dimensions among Mexican university students. A systematic review was carried out based on the analysis of documents according to the PRISMA model, searching for original articles that made use of the Ryff scale (1989) and showed the results by high, medium, or low degree. The SciELO, Redalyc, Dialnet, PubMed, and ProQuest databases were explored, finding 149 documents, leaving a total of 4 publications for analysis. The results show average degrees of global psychological well-being and its dimensions. The study of psychological well-being in university students is extremely important since observing the levels of this construct in this population can help institutions, tutors, or student guides to carry out strategies and set goals in order to improve academic performance and personal development.